The impacts of COVID-19 lockdown on PM10 and SO2 concentrations and association with human mobility across Turkey - ORAK, NUR HANİFE (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2021)
The SARS-CoV-2 virus pandemic (COVID-19) has caused 2.25 million deaths worldwide by February 3, 2021 (JHU, 2021) and still causing severe health and economic disruptions with increasing rates. This study investigates the impact of lockdown measures on ambient air pollution and its association with human mobility in 81 cities of Turkey. We conducted a countrywide analysis using PM10 and SO2 measurement data by the Turkish Ministry of Environment and Urbanization and mobility data derived from cellular device movement by Google. We observed the most significant change in April 2020. PM10 and SO2 concentrations were lower in 67% and 59% of the cities, respectively in April 2020 compared to the previous five years (2015-2019). The correlation results show that Restaurant/Cafe ', Transit, and Workplaces mobility is significantly correlated with PM10 and SO2 concentration levels in Turkey. This study is the first step of a long-term investigation to understand the air quality impacts on population susceptibility to COVID-19.
Keywords: SARS-CoV-2; COVID-19 pandemic; Air quality; Mobility; Turkey